Pengaruh Penguatan Nilai Sabar Dan Syukur Serta Manajemen Konflik Terhadap Keharmonisan Antar Siswa - Nini Paramida; Sudirman Dianto; Saripah; Muhammad Alfi Syahrin (Educational Research Center, 2026)
This study aims to analyze the influence of patience values, gratitude values, and conflict management on harmony among students at SMAN 17 Segulung. This research employed a quantitative approach with an explanatory design. The population of the study consisted of all students of SMAN 17 Segulung, with the sample determined using proportionate stratified random sampling. Data were collected through questionnaires developed using a Likert scale, while data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics 26. The results showed that gratitude values had a positive and significant effect on harmony among students (p < 0.05). Conflict management also had a positive and significant effect on harmony among students (p < 0.05). In contrast, patience values showed a positive but not partially significant effect (p > 0.05). Simultaneously, patience values, gratitude values, and conflict management had a significant effect on harmony among students, with a coefficient of determination (R²) of 0.752. These findings indicate that harmony among students is influenced not only by social skills but also by religious character developed within students. This study emphasizes the importance of integrating character education and social skill development in creating a harmonious and conducive school environment.